2020
DOI: 10.1101/2020.04.22.055061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Megaevolutionary dynamics in reptiles and the role of adaptive radiations in evolutionary innovation

Abstract: 13Adaptive radiations are long believed to be responsible for the origin of phenotypic diversity and 14 new body plans among higher clades in the fossil record. However, few studies have assessed 15 rates of phenotypic evolution and disparity across broad scales of time to understand the 16 evolutionary dynamics behind the origin of major clades, or how they relate to rates of molecular 17 evolution. Here, we provide a total evidence approach to this problem using the largest available 18 data set on diapsid r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 63 publications
(106 reference statements)
1
6
0
Order By: Relevance
“…A similar pattern of high evolutionary rates and subsequent deceleration have been found in mammaliamorphs (Close et al, 2015), whereas rather constant rates have been found for lepidosaurs in the Early Jurassic (Simões et al, 2020). The increase of evolutionary rates-which is stronger for the pelvis-recovered here for archosauromorphs during the Middle and Late Jurassic partially matches the results found for lepidosaurs, but the latter show a conspicuous deceleration in the Late Jurassic (Simões et al, 2020). By contrast, mammaliamorphs depict a continuous decrease of rates during the Middle and Late Jurassic (Close et al, 2015).…”
Section: Median Rates Through Time Radiation and Extinctionsupporting
confidence: 70%
See 1 more Smart Citation
“…A similar pattern of high evolutionary rates and subsequent deceleration have been found in mammaliamorphs (Close et al, 2015), whereas rather constant rates have been found for lepidosaurs in the Early Jurassic (Simões et al, 2020). The increase of evolutionary rates-which is stronger for the pelvis-recovered here for archosauromorphs during the Middle and Late Jurassic partially matches the results found for lepidosaurs, but the latter show a conspicuous deceleration in the Late Jurassic (Simões et al, 2020). By contrast, mammaliamorphs depict a continuous decrease of rates during the Middle and Late Jurassic (Close et al, 2015).…”
Section: Median Rates Through Time Radiation and Extinctionsupporting
confidence: 70%
“…The stabilization (cranium) or increase (pelvis) of evolutionary rates since the Toarcian is likely related to the mass extinction event and the diversification of the group as a result of the occupation of empty niches (Benton, 1983;Brusatte et al, 2008a;Brusatte et al, 2008b;Irmis, 2010). A similar pattern of high evolutionary rates and subsequent deceleration have been found in mammaliamorphs (Close et al, 2015), whereas rather constant rates have been found for lepidosaurs in the Early Jurassic (Simões et al, 2020). The increase of evolutionary rates-which is stronger for the pelvis-recovered here for archosauromorphs during the Middle and Late Jurassic partially matches the results found for lepidosaurs, but the latter show a conspicuous deceleration in the Late Jurassic (Simões et al, 2020).…”
Section: Median Rates Through Time Radiation and Extinctionmentioning
confidence: 75%
“…We used the Mkv + gamma substitution model [43] (Mk with ascertainment bias correction) for the morphological data of datasets 1 and 2. The molecular partition of the combined evidence dataset (dataset 2) was analysed under the GTR + gamma model and subdivided into four partitions, following the previous partitioning and model test analyses for this dataset [11,35].…”
Section: Bayesian Inference Analysesmentioning
confidence: 99%
“…Recent additions and revisions to the early squamate and rhynchocephalian fossil records made possible by the use of new imaging and analytical tools have substantially improved our understanding of squamate origins and the rise of squamates to ecological dominance as rhynchocephalian diversity declined [6][7][8][9][10]. Reconstructing the divergence times of living squamate clades has been greatly aided by the reconciliation of major differences among phylogenies of squamates produced using morphological and molecular data [1,5,7,9,11]. These advances have consistently inferred a Triassic (approx.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation